1998
DOI: 10.1023/a:1011964213024
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pluronic P85 unimers increase accumulation of a P-gp-dependent drug in Caco-2 monolayers through inhibition of the P-gp efflux system. The mechanism of the micelle effect is not known, however, it is very similar to the micelle effects in BBMEC. This has been previously shown to involve vesicular transport of the micelle-incorporated drug. The study suggests that Pluronic copolymers can be useful in increasing oral absorption of select drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(28 citation statements)
references
References 13 publications
0
27
1
Order By: Relevance
“…Moreover, pharmaceutical excipients such as PluronicF127 and Tween80 that we used in this study are known to have the ability to modulate the P-gp-mediated efflux of low permeable drugs. [24][25][26] Morin-loaded mixed micelle formulation consisting of morin-PluronicF127-Tween80=1 : 10 : 0.02 (w/w/w) was developed and the bioavailability of morin using this formulation was dramatically increased from 0.35% (in case of morin itself) to 11.62% (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pharmaceutical excipients such as PluronicF127 and Tween80 that we used in this study are known to have the ability to modulate the P-gp-mediated efflux of low permeable drugs. [24][25][26] Morin-loaded mixed micelle formulation consisting of morin-PluronicF127-Tween80=1 : 10 : 0.02 (w/w/w) was developed and the bioavailability of morin using this formulation was dramatically increased from 0.35% (in case of morin itself) to 11.62% (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Block copolymer poly(ethylene oxide)-bpoly(propylene oxide)-b-poly(ethylene oxide) (PEO-PPO-PEO, or pluronic 123 copolymer, or P123) is used as carrier material for solubilization and delivery of drug in view of its non-toxicity, nonimmunogenicity and biocompatibility [35]. Moreover, the high proportion of hydrophobic block could account for ideal drug loading ability of P123 [36][37][38]. As amphipathic molecule, both ST and P123 could self-assemble to form micelles in aqueous solution [39].…”
Section: Introductionmentioning
confidence: 99%
“…2): a first region (0.1-5 kGy), where the CP value does not show significant changes, and a second region (5-50 kGy), characterized by a roughly linear decrease of CP. It is worthy to note that at higher doses (70 kGy), the CP value remains almost constant, and that the range where greater changes are observed is precisely the one comprising typical sterilization doses (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Effect Of Gamma Radiation On the Cloud Pointmentioning
confidence: 97%
“…On the other hand, some attempts have been made to identify the physicochemical parameters of surfactants that would be predictive for their absorption-enhancing properties in formulations to increase the absorption of drugs by different organs [14]. These parameters included hydrophilic-lipophilic balance (HLB), CMC, surfactant structure, and the surfactant surface activity [15][16][17]. Other investigations of liquid formulations containing nonionic surfactant have showed that the cloud point of the surfactant can be a key parameter for consideration, and it can be modulated through the proper choice of excipient [18].…”
Section: Introductionmentioning
confidence: 99%